BUSINESS MODEL FORMULATION FOR E-NEWSPAPER IN INDONESIA (CASE STUDY: PIKIRAN RAKYAT) - Aditia Sovia Pramudita; Amri Yanuar; Tamadara Hilman (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
The newspaper industry is undoubtedly entering a declining period. Changes in customer behavior become a major problem for newspaper companies. Demand for electronic media is increasing every year. The electronic newspaper is the only way for newspaper companies to survive in this industry. This study aims to formulate an economically sustained business model through value chain analysis and business model canvas. The research methods used in this study are interviews and consolidation studies. Two main concepts are being used in this research, namely, value chain analysis and business model canvas. Benchmarking with sustained online media company is also needed. The results of this study are business model from the related company that has been economically sustained based on profitability ratio that can be adopted for Pikiran Rakyat e-newspaper. Based on the framework, business model recommendations must be able to define consumers into two, namely audience and advertiser, and determine how to monetize it as a revenue stream. There are two stages in the development of recommended business model from this study; the first stage Pikiran Rakyat needs to focus on community models to gain audiences and then switch into advertising models gradually to monetize their audience. At last, e-newspaper is recommended as an online media commerce model to widen the possibility of revenue stream`s choices.